Effect of renin‐angiotensin system antihypertensive medication use on cognitive function in diabetes mellitus with obesity or overweight: An ancillary study to the Action for Health in Diabetes (Look AHEAD) trial. Issue 12 (5th September 2022) - Wharton, Whitney; Anderson, Andrea; Hayden, Kathleen M.; Carmichael, Owen T; Clark, Jeanne M; Luchsinger, José A.; Espeland, Mark; Yasar, Sevil
Abstract: Aim: To determine whether antihypertensive medication (AHM) acting through the renin angiotensin system (RAS‐AHM), compared with other AHM, can mitigate effects on cognitive function and risk for impairment in a population with type 2 diabetes mellitus (T2DM). Materials and Methods: This secondary analysis of the randomized controlled Action for Health in Diabetes (Look AHEAD) study included 712 community‐dwelling participants who were followed over 15 years. Logistic regression was used to relate RAS‐AHM use to cognitive impairment, and linear regression was used to relate RAS‐AHM use to domain‐specific cognitive function after adjusting for potential confounders. Results: A total of 563 individuals reported RAS‐AHM use and 149 reported other‐AHM use during the study. RAS‐AHM users have college or higher education (53%), had higher baseline glycated haemoglobin (57 mmol/mol), and reported higher diabetes medication use (86%), while other‐AHM users were more likely to be White (72%), obese (25%) and to have cardiovascular history (19%). RAS‐AHM use was not associated with a reduced risk of dementia compared with other‐AHM use. We did observe better executive function (Trail Making Test, part B, P  < 0.04), processing speed (Digit Symbol Substitution Test, P  < 0.004), verbal memory (Rey Auditory Verbal Learning Test‐delayed recall, P  < 0.005), and composite score ( P  < 0.008) among RAS‐AHM users compared with other‐AHM users. Conclusion: In this sample of adults with T2DM, free of dementia at baseline, we observed a slower decline in processing speed, executive function, verbal memory, and composite score among RAS‐AHM users.